The experiences of participating in winter among youths with a physical disability compared with their typically developing peers. (11th December 2014) - Lindsay, S.; Morales, E.; Yantzi, N.; Vincent, C.; Howell, L.; Edwards, G.
Abstract: Background: Having a physical disability and using a wheelchair can create difficulties in navigating the physical and built environment, especially during winter when snow and ice become problematic. Little is known about the experiences of winter among youth who use an assistive mobility device. This study aimed to understand how youth with a physical disability experience winter, compared with typically developing peers. Methods: A purposive sample of 25 youths (13 with a physical disability; 12 typically developing) completed a 2‐week weather journal and photographs in two Canadian cities during winter. These data were used to guide semi‐structured interviews with participants. Results: Youths with disabilities experienced many similar challenges in winter, such as health and safety concerns and accessibility issues, compared with typically developing youth – but to a greater extent. Youths with disabilities reported more challenges going outdoors during winter and negative psychosocial impacts, including loneliness and increased dependence, compared with peers without a disability. They also, however, described developing several adaptive strategies to cope with these challenges. Conclusions: There is a strong need to remove physical and environmental barriers to facilitate the participation and inclusion of youth with disabilities in winter.